Physical Properties of Fe3Si Films Coated through Facing Targets Sputtering after Microwave Plasma Treatment - Nattakorn Borwornpornmetee; Peerasil Charoenyuenyao; Rawiwan Chaleawpong; Boonchoat Paosawatyanyong; Rungrueang Phatthanakun; Phongsaphak Sittimart; Kazuki Aramaki; Takeru Hamasaki; Tsuyoshi Yoshitake; Nathaporn Promros (My University, 2021)
Fe3Si films are deposited onto the Si(111) wafer using sputtering with parallel facing targets. Surface modification of the deposited Fe3Si film is conducted by using a microwave plasma treatment under an Ar atmosphere at different powers of 50, 100 and, 150 W. After the Ar plasma treatment, the crystallinity of the coated Fe3Si films is enhanced, in which the orientation peaks, including (220), (222), (400), and (422) of the Fe3Si are sharpened. The extinction rule suggests that the B2–Fe3Si crystallites are the film’s dominant composition. The stoichiometry of the Fe3Si surfaces is marginally changed after the treatment. An increase in microwave power damages the surface of the Fe3Si films, resulting in the generation of small pinholes. The roughness of the Fe3Si films after being treated at 150 W is insignificantly increased compared to the untreated films. The untreated Fe3Si films have a hydrophobic surface with an average contact angle of 101.70°. After treatment at 150 W, it turns into a hydrophilic surface with an average contact angle of 67.05° because of the reduction in the hydrophobic carbon group and the increase in the hydrophilic oxide group. The hardness of the untreated Fe3Si is ~9.39 GPa, which is kept at a similar level throughout each treatment power.
Keywords: Metal and Thin Film Mechanics